PENGARUH PENGGUNAAN VIDEO ANIMASI BERBASIS CERITA RAKYAT TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN 1 MATANG SEULIMENG LANGSA - Amanda, Yulistika; Siregar, Waliyul Maulana; Gandamana, Apiek; Hatmi, Edizal; Winara (STAIN Bengkalis, 2025)
This research is motivated by the low learning outcomes of students in the subject of Pancasila Education. This study aims to determine the effect of the use of folklore-based animation videos on the learning outcomes of Pancasila education on the material of Pancasila values in the daily life of grade V of SD Negeri 1 Matang Seulimeng Langsa. The research was carried out using a type of quantitative research and experimental method. The research population is all grade V students of SD Negeri 1 Matang Seulimeng totaling 60 students. Using the Purposive Sampling technique, the students of the VB (Experiment) class amounted to 33 students and the VA (Control) class amounted to 27 students. The results of the normality test showed that the Pretest value of the experimental class obtained a significance value (Sig) of 0.062 > 0.05 and the Pretest value of the control class of 0.448 > 0.05. And for the Posttest value, the experimental class had a Sig value of 0.079 > 0.05 and the postest control class 0.178 > 0.05. It is stated that both groups are normally distributed. In the homogeneity test for the control class with a significance value of 0.818 > 0.05 and for the experimental class 0.213 > 0.05. It is stated that the pretest and post test data have the same variant. The hypothesis test was carried out using the paired sample t test. The results of the t calculation of the > t table were obtained which were 9,429 > 2,036, which means that there was an influence of folklore-based animation videos on the learning outcomes of Pancasila Education students in grade V of SDN 1 Matang Seulimeng Langsa.